Male mites are the promising targets for control of Dermanyssus gallinae (Acari: Dermanyssidae) based on the reproductive biology research - Liu, Boxing; He, Jiaqi; Liu, Qi; Wang, Bohan; Xiong, Mingjun; Sun, Weiwei; Pan, Baoliang (Veterinary parasitology, 2025)
Dermanyssus gallinae is a significant hematophagous ectoparasite affecting laying hens. However, due to the limitations of research methods, especially feeding methods, the reproductive biology of D. gallinae has not been fully studied. In this study, two recently developed in vivo feeding methods were employed to investigate the reproductive biology of D. gallinae, including the impacts of mating on feeding status and egg laying, the reproductive capacity of female mites, the mating capacity of male mites and the sex ratio of offspring. The results demonstrated that only mated adult female mites were able to reach an engorged state and were capable of oviposition. The maximum egg-laying times for an adult female mite was 13, with an average of 44.39 eggs per mite. Moreover, for the first time, this study described the mating ability of adult male mites. On average, a male mite can mate with 16 female mites during its lifetime and the average mating period is 8.47 d. All offspring from the first batch of eggs produced by novel adult female mites were males. Afterward, the proportion of male offspring mites gradually decreases with the generation. The results show that the males play a crucial role in the population establishment of D. gallinae, indicating they can be considered promising targets for the mite control. [Display omitted] •The reproductive parameters of female mites were updated.•The mating ability of male mites were described for the first time.•Male plays a crucial role in mite population establishment process.•Male mites are promising targets for control measures.